The Implementation of Senior High School Alternative Learning System: Basis for a Proposed Professional Development Plan for Teachers - Avegail Paez (Philippine Association of Institutions for Research, Inc., 2024)
The study assessed the Alternative Learning System (ALS) in Bulacan, focusing on learning delivery, resources, environment, and assessment to propose a professional development plan for teachers. Utilizing a mixed-methods approach, data were collected from 342 ALS implementers and learners through surveys and interviews. Findings revealed a diverse teacher demographic, predominantly female and single, with most having less than five years of experience and no recent seminar attendance. Most teachers held Bachelor's degrees, with some possessing Master's degrees, and a majority had passed the LET exam. Respondents rated ALS implementation as "fully implemented," except for learners who rated the learning delivery and learning resources as "implemented". As for significant differences among the respondents, ALS implementation has no significant differences among the four learning domains. Challenges included limited interaction, ineffective communication, curriculum mismatches, resource constraints, and high workloads. Overall, there was consensus on ALS implementation across respondent groups, highlighting strengths and areas needing improvement to enhance the program's effectiveness and teacher support. To effectively address the challenges the ALS program faces, it is essential to enhance instructional delivery through increased face-to-face interaction between students and teachers, alongside providing targeted training on ALS pedagogy for educators. Developing effective learning materials, ensuring adequate facilities, creating a separate ALS curriculum, and establishing clear assessment policies will help minimize distractions, support student engagement, and improve overall learning outcomes.